The denial of motherhood to pregnant disappeared detainees (School of Naval Mechanics, 1976-1983) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This project aims to analyze the construction and operation of a clandestine maternity unit within the School of Naval Mechanics/ Escuela de Mecánica de la Armada (ESMA), as a specific feminine space, during the last military dictatorship in Argentina. The goal for this space was to guarantee the pregnancies of and births by women who were detained-disappeared and, at the same time, deny their ability to raise their children (through the appropriation of minors). The article aims to investigate the practices, structures, and recurrent processes regarding the treatment of these women as well as the management of their births and hand- ling of their children within this clandestine detention center.
Keywords: appropriation of children, captivity, dictatorship, maternity